The Commemoration of Independence Day: Recalling Indonesian Traditional Games - Fitri, Mustika; Nur, Hana Astria; Putri, Wulandari (Frontiers in Psychology, 2020)
Traditional games in Indonesia are one of the cultural heritages the existence of which should be protected and preserved. The purpose of this study was to preserve the cultural diversity by recalling the traditional games through the commemoration of Indonesia Independence Day that is conducted annually. The Online Ethnography method was used in this research by administering text analysis and interview. The result of the study showed that traditional games held during the commemoration of Indonesia Independence Day could help recall the form and the rules of traditional games that are annually conducted during the commemoration in different regions. The result also showed that the traditional games held in the commemoration of Indonesia Independence Day indirectly built a bonding of the people through the value of togetherness, cooperation, and solidarity among the member of the society. Furthermore, the games reflected the cultural diversity of Indonesia, where every region has different names and rules of the traditional games.